Algae in the database of world collections of living cultures WDCM CCINFO - Комариста, В. П.; Горбулін, О. С.; Догадіна, Т. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
There was analyzed how algae are presented in world collections of living cultures according to CCINFO database. The shortcomings of CCINFO database were revealed: empty, false and duplicate records, not all collections presented in the consolidated directory. The current 6th version of the database contains 2307 species of algae (about 5% of the known natural diversity) and 142 intraspecific taxa, living cultures of which are supported in 12 collections; 293 cultures are not identified to species. More than half of the cultures in the world's largest collections are unique and not duplicated in the other collections. Taxonomic diversity of algae is reflected unevenly in the culture: Diatoms, Brown, Red and Dinophyta algae are poorly represented; Green algae are represented in the culture best. It is proposed to consider the autecology data when isolating algae into the culture to expand and upgrade the funds of the collections.